Enhancing Clinical Content and Race/Ethnicity Data in Statewide Hospital Administrative Databases: Obstacles Encountered, Strategies Adopted, and Lessons Learned. (26th June 2015) - Pine, Michael; Kowlessar, Niranjana M.; Salemi, Jason L.; Miyamura, Jill; Zingmond, David S.; Katz, Nicole E.; Schindler, Joe
Abstract : Objectives: Eight grant teams used Agency for Healthcare Research and Quality infrastructure development research grants to enhance the clinical content of and improve race/ethnicity identifiers in statewide all‐payer hospital administrative databases. Principal Findings: Grantees faced common challenges, including recruiting data partners and ensuring their continued effective participation, acquiring and validating the accuracy and utility of new data elements, and linking data from multiple sources to create internally consistent enhanced administrative databases. Successful strategies to overcome these challenges included aggressively engaging with providers of critical sources of data, emphasizing potential benefits to participants, revising requirements to lessen burdens associated with participation, maintaining continuous communication with participants, being flexible when responding to participants' difficulties in meeting program requirements, and paying scrupulous attention to preparing data specifications and creating and implementing protocols for data auditing, validation, cleaning, editing, and linking. In addition to common challenges, grantees also had to contend with unique challenges from local environmental factors that shaped the strategies they adopted. Conclusions: The creation of enhanced administrative databases to support comparative effectiveness research is difficult, particularly in the face of numerous challenges with recruiting data partners such as competing demands on information technology resources. Excellent communication, flexibility, and attention to detail are essential ingredients in accomplishing this task. Additional research is needed to develop strategies for maintaining these databases when initial funding is exhausted.